Antifungal efficacy of three medicinal plants Glycyrrhiza glabra, Ficus religiosa, and Plantago major against oral Candida albicans: A comparative analysis - Hunny Sharma; G Y Yunus; Rohit Agrawal; Monika Kalra; Swati Verma; Supriya Bhattar (Wolters Kluwer Medknow Publications, 2016)
Introduction: From ancient times, plants with medicinal values are being tested and used in the treatment of various infectious diseases. Aims and Objectives: The present in vitro study was designed to assess the antifungal activity of three commonly available medicinal plants Glycyrrhiza glabra, Ficus religiosa, and Plantago major on inhibiting oral Candida albicans in comparison to standard antifungal agents. Materials and Methods: Bark of G. glabra, stem of F. religiosa, and husk of P. major were collected, crushed into fine powder, and dissolved in 67% ethanol. Extracts were subjected to antifungal efficacy test against oral C. albicans (ATCC 66027) using Kirby-Bauer disc diffusion method. Mean zone of inhibition (ZOI) was measured by HI antibiotic zone scale. One-way ANOVA using Tukey's post hoc and t-test were applied for statistical analysis. Results: G. glabra was found to be most effective among the three with highest mean ZOI measuring 19.8 ± 0.83, 19.4 ± 0.54, and 18.2 ± 1.09 at 24, 48, and 72 h, respectively. Tukey's post hoc test showed statistically nonsignificant difference between antifungal activity of F. religiosa and P. major with itraconazole 10 mcg. Conclusion: G. glabra, F. religiosa, and P. major showed acceptable potency against C. albicans (ATCC 66027) comparable to that of synthetic antifungal agents. However, further studies should be undertaken to affirm the same and test their efficacy in different concentrations and clinical utility.